Acceptability of app-based contact tracing for COVID-19: cross-country survey evidence - Altmann, S; Milsom, L; Zillessen, Z; Blasone, R; Gerdon, F; Bach, R; Kreuter, F; Nosenzo, D; Toussaert, S; Abeler, J (JMIR Publications, 2020)
Background: The COVID-19 pandemic is the greatest public health crisis of the last 100 years. Countries have responded with various levels of lockdown to save lives and stop health systems from being overwhelmed. At the same time, lockdowns entail large socioeconomic costs. One exit strategy under consideration is a mobile phone app that traces the close contacts of those infected with COVID-19. Recent research has demonstrated the theoretical effectiveness of this solution in different disease settings. However, concerns have been raised about such apps because of the potential privacy implications. This could limit the acceptability of app-based contact tracing in the general population. As the effectiveness of this approach increases strongly with app uptake, it is crucial to understand public support for this intervention.